Review of Reduced-Order Models for Online Protection of Water Distribution Networks - Cheima Djemel; Olivier Piller; Thierry Horsin; Chloé Mimeau; Iraj Mortazavi (Engineering Proceedings)
This paper presents a review of reduced-order models (ROMs) and digital twins, with a primary focus on their application to water distribution networks (WDNs). Initially, we concentrated on the physical modelling of WDNs. Following this, we introduced relevant programming, specifically addressing WDNs and solving equations for extended-period simulations. This paper then explored various ROM methods outlined in the existing literature. Lastly, we highlighted recent initiatives in the implementation of digital twins and approaches aimed at reducing uncertainty.